Insect Pests Associated with Grewia Optiva Drummond in Solan District of Himachal Pradesh - Sharma, Ajay; Sood, Anil (Indian Forester, 2009)
Grewia optiva is an important fodder tree in Solan District of Himachal Pradesh. It forms an important component of agro forestry systems in the mid hill region because of its multipurpose use as fodder, fuel and fibre. Its leaves are damaged badly by different insects leading to huge losses of green fodder. The different insect pests found feeding on G. optiva are Mimastra cyanura, Myllocerus setulifer, Apoderus spp. Lygropia obrinusalis, Adoretus bimarginatus etc. These pests take heavy toll of the foliage and results in huge losses to the farmers.